Ethanol and methanol gas sensing properties of ZnO microrods. (2019) - Sinha, M.; Mahapatra, R.; Ghosh, R.
Abstract: In this study, ZnO microrods with the diameter of 250nm-3µm were synthesized by low temperature (95°C) wet chemical process on SiO2 /Si substrate. The gas sensing properties using ZnO microrods towards ethanol and methanol were studied at different operating temperatures (100, 150 and 200°C). The experimental results show the maximum sensitivity about 7.83×10 4 % and 9.08×10 4 % to 400 ppm methanol and ethanol gas, respectively at an operating temperature of 150°C. A fast response time and recovery time of methanol and ethanol gases have also been found. The response and recovery time decrease with increase in temperature.